Access to provisioning services by local communities from Mpanga central forest reserve in central Uganda - Gumoshabe, Memory; Anywar, Godwin; Tugume, Patience (Frontiers in Forests and Global Change, 2023)
Forest resources are an important source of products on which rural communities depend for survival. Mpanga Central Forest Reserve (CFR) is a valuable resource to adjacent communities through provision of different goods and services for subsistence and income generation. It also services as an important eco-tourist site. However, there is scanty information regarding the products obtained from Mpanga CFR and their contribution to livelihoods of adjacent communities. The study explored the provisioning services obtained from the CFR, assessed the contribution of the CFR to the surrounding communities and explored the challenges faced while obtaining these services from the forest reserve. Provisioning services are the material benefits supplied by the ecosystem. A total of 116 respondents were randomly selected from 11 villages in Kamengo sub-county Mpigi District and interviewed using semi-structured questionnaires. The residents obtained wild foods, medicinal herbs, fuelwood, construction and carving materials. Most of the respondents used obtained products for subsistence (51%) while the rest sold them. Regression analysis revealed that 76.5% of the variability in cash income from the CFR is significantly be explained by age of respondents, period of stay and education level (F= 90.429, P<0.005). Increase in age and educational level of respondents reduced ability to obtain cash income from the forest by (β = -0.19) and (β = -0.625) respectively but increase in period of stay acted in the reverse (β= 0.22). Despite the importance of provisioning services in improving the livelihood of communities adjacent the forest, some challenges in accessing the forest were reported. The quantities of some extracted species had declined over a five-year period resulting in reduction of household income. This negatively impacts on the livelihoods of the young and uneducated that depend on forest activities for income generation. It is pertinent that alternative livelihood options are sought to address this trend. Also, forest management strategies should provide a win-win situation to forest managers and communities adjacent to these forests. This will not only preserve the forest resource but will also ensure a sustainable livelihood to forest dependent communities.